TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.